2013
DOI: 10.1111/hepr.12167
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating Lin−/lowCD33+HLA‐DR myeloid‐derived suppressor cells in hepatocellular carcinoma patients

Abstract: Our study provides evidence showing an increased population of Lin(-/low) CD33(+) HLA-DR(-) MDSC in the peripheral blood of HCC patients. Our data also suggest that MMP-13 and COX-2 in PBMC may play a new important role companied with MDSC in HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 48 publications
(118 reference statements)
5
46
0
Order By: Relevance
“…It has been reported that MDSCs in peripheral blood are increased in patients with hepatocellular carcinoma2930, and we have similar results in this study. Our data demonstrated that the frequency of PD-L1 + MDSCs increased in HCC patients.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that MDSCs in peripheral blood are increased in patients with hepatocellular carcinoma2930, and we have similar results in this study. Our data demonstrated that the frequency of PD-L1 + MDSCs increased in HCC patients.…”
Section: Discussionsupporting
confidence: 92%
“…Neoplastic cells have additional elaborate mechanisms to subvert antitumor T cell activity, for example the induction of host immunosuppressive cells, including MDSCs and regulatory T cells, and MDSCs have been identified in a variety of human malignancies (36). Immunosuppression is not limited to the tumor microenvironment, and circulating myeloid cells capable of inducing dysfunctional immune responses have been repeatedly described (37,38). Therefore, the levels of circulating MDSCs were evaluated, to determine their effect on MAGE-A4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of MDSCs has been acknowledged in primary tumor formation (119), extensive data connect MDSC expansion to more advanced cancer stages (120). MDSC numbers are associated with clinical stage in bladder carcinoma (121), pancreatic adenocarcinoma (122), hepatocellular carcinoma (123,124), gastric cancer (125), NSCLC (126), and head and neck squamous cell carcinoma (127), as well as in hematological malignancies such as non-Hodgkin lymphoma (128). Collectively, these results indicate that expansion of MDSCs in cancer patients is a general phenomenon accompanying tumor progression.…”
Section: Prognostic Significance Of Myeloid Cells In Cancer Patientsmentioning
confidence: 99%